FACE AND CONSTRUCT VALIDITY OF THE CARDIFF WOUND IMPACT INSTRUMENT ON THE PATIENTS WITH DIABETIC FOOT ULCERS - Yuliaty, Rina (ETN Centre Indonesia, 2016)
Background: Diabetic foot ulcer is one of the diabetes mellitus complications that impact on the patient's life. Cardiff Wound Impact (CWI) is one of instruments that can measure the impact of chronic wounds. The purpose of this study was to evaluate and validate the Cardiff Wound Impact in diabetic foot ulcers in Indonesia population. Methods: This research used cross-sectional method and used 51 samples of diabetic foot ulcers patients in Sulianti Saroso hospital, Wocare Clinic and Husada hospital. The respondents filled the Cardiff Wound Impact Questionnaire. In the face validity there was no significant problems in terms of language and meaning of a sentence. Construct validity was performed by using factor analysis. Results: The data showed that the value of Kaiser-Meyer-Olkin Measure of Sampling Adequacy (KMO) and Bartlet Test of each component of CWI were in the range of 0.741 to 0.834. The results of this study also showed a strong correlation between the scale of quality of life and satisfaction of quality of life (p = 0005; r = 0.764). Conclusion: This study has shown that the CWI is a valid and reliable tool to assess the impact of the diabetic foot ulcer in Indonesia because it has been tested through the face and construct validity. Researcher suggested that this research need to be done again with the same proportion between outpatients and inpatients wards. Keywords: Cardiff Wound Impact, construct validity, diabetes mellitus, diabetic foot ulcer